2015
DOI: 10.1002/anie.201411688
|View full text |Cite
|
Sign up to set email alerts
|

Unwinding of the C‐Terminal Residues of Neuropeptide Y is critical for Y2 Receptor Binding and Activation

Abstract: Despite recent breakthroughs in G protein-coupled receptor (GPCR) structure characterization, there is only sparse data on how GPCRs recognize larger peptide ligands. Here, we integrate nuclear magnetic resonance (NMR) spectroscopy, molecular modeling, and double-cycle mutagenesis studies to obtain a structural model of the peptide hormone neuropeptide Y (NPY), bound to its human G protein-coupled Y2 receptor (Y2R). Solid-state NMR measurements of specifically isotope-labeled NPY in complex with in vitro folde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
146
1
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 74 publications
(166 citation statements)
references
References 25 publications
10
146
1
9
Order By: Relevance
“…In contrast, the NPY-bound model shows that side chain of Q120 3.32 points almost in the opposite direction and engages in a hydrogen bond with the hydroxy group of Y36-NH 2 (Extended Data Fig. 1d), similar as the interaction between the Y 2 R residue Q 3.32 and NPY suggested by Xu et al 28 In Y 2 R, it was also reported that Q 3.32 may interact with the C-terminal amide of NPY 16 . IP accumulation studies show that the Y 1 R mutation Q120 3.32 H leads to a 26-fold decrease in potency of NPY, and NPY-tyramide lacking the C-terminal amide displays a 45-fold loss of activity.…”
supporting
confidence: 61%
See 4 more Smart Citations
“…In contrast, the NPY-bound model shows that side chain of Q120 3.32 points almost in the opposite direction and engages in a hydrogen bond with the hydroxy group of Y36-NH 2 (Extended Data Fig. 1d), similar as the interaction between the Y 2 R residue Q 3.32 and NPY suggested by Xu et al 28 In Y 2 R, it was also reported that Q 3.32 may interact with the C-terminal amide of NPY 16 . IP accumulation studies show that the Y 1 R mutation Q120 3.32 H leads to a 26-fold decrease in potency of NPY, and NPY-tyramide lacking the C-terminal amide displays a 45-fold loss of activity.…”
supporting
confidence: 61%
“…NPY-tyramide was synthesized as previously described 44 . Isotopically labelled NPY variants were prepared as described 16 , and 13 C/ 15 N labelled amino acids were coupled manually with 2 eq. HOBT/DIC in DMF over night.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations